PENGARUH KUALITAS DAN HARGA PERUMAHAN KOTA CITRA GRAHA TERHADAP MINAT BELI MASYARAKAT - Abdul Kadir Kadir (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Abstract, The main objective in this study is to examine and analyze (1) the effect of quality and price on people's buying interest in Citra Graha City housing. (2) the effect of quality on people's buying interest in Citra Graha City housing. (3) the effect of prices on people's buying interest in Citra Graha City housing. (4) To see which variable has greater influence on people's buying interest in Citra Graha City housing. The targets in this study include (1) To be able to see how much influence the two variables in this study are quality and price in influencing public buying interest in Citra Graha City housing. (2) Being a reference material for consumers to be able to determine the purchasing policy after knowing about the quality and price set by the City of Citra Graha. (3) From the results of this study, it can be used as a reference as a policy making in product pricing strategies. (4) Making the results of this research as textbook reference material, especially in the field of marketing management. This research was conducted with a quantitative method and using the analysis method with SPSS Windows For Data as a data analysis tool. To facilitate the justification, a 5-point Likert scale is used. Likert scale is a scale used in questionnaires to facilitate respondents in answering questions, then respondents answer questions in accordance with the code in the questionnaire. Before testing with regression analysis, the research data were tested with a classic assumption test consisting of: normality test, heterokedasticity test, and multicollinearity test. Then for simultaneous hypothesis testing using the F test, and for partial hypothesis testing using the t test. Meanwhile, to determine the most dominant variable affecting the level of employee job satisfaction using the standardized coefficient beta. Based on the results of the study it can be found that the variable of quality and price is very significant in influencing the buying interest of consumers or prospective consumers to be able to purchase housing units in the City of Citra Graha, this can be proven with a probability level of more than 0.05 or less than 5%. In addition to the level of probability can also be proven by table 5.8 it turns out that F count is greater (33,108) than F table (2.3092), so the decision is to reject H0 and accept Ha, which means the variables X1, X2 together affect the consumer's buying interest will the purchase of housing units in the City of Citra Graha. Job Characteristics Variable has a significant and positive effect on the level of employee job satisfaction with a significance level of 0.473 or 47.3%. This means that if the characteristics of this work are considered it will increase employee job satisfaction by 47.3%.